The influences of ship speed and separating distance on ship-bank effect using CFD (Latakia University Journal -Engineering Sciences Series, 2022)
The bank effect is one of the most dangerous phenomena with regard to navigation in waterways and ports.The aim of this research is to analyze the effect of the bank and determine its relationship with the ship’s speed and it's distance from the bank, given that the ship’s speed and the ship’s distance from the bank are the most important parameters that affect the ship-bank effcet. the RANS (Reynolds Averaged Navier Stokes) method with the κ-ω model and the implicit SST shear stress transfer scheme method was used to solve Navier Stokes equations due to the quality and stability it provides to the solution.A comparison between the numerical results and the experimental ones, showed the accuracy of the calculations in predicting the forces and moments resulting from the phenomenon of the bank effect.